Effect of a spray formulation on the reproductive parameters of a susceptible population of Rhipicephalus (Boophilus) microplus - Cruz, Breno Cayeiro [UNESP]; Zanetti Lopes, Welber Daniel [UNESP]; Maciel, Willian Giquelin [UNESP]; Felipelli, Gustavo [UNESP]; Pires Teixeira, Weslen Fabricio [UNESP]; Favero, Flavia Carolina [UNESP]; Prando, Luciana [UNESP]; Buzzulini, Carolina [UNESP]; Sorares, Vando Edesio [UNESP]; Costa Gomes, Lucas Vinicius [UNESP]; Bichuette, Murilo Abud [UNESP]; Costa, Alvimar Jose da [UNESP] (Brazilian Coll Veterinary Parasitology, 2014)
The number of studies emphasizing the possible damage that acaricidal spray formulations can cause on engorged female ticks'reproductive parameters is small. The present study evaluated the deleterious effects of a spray formulation (dichlorvos 60% + chlorpyrifos 20%) on the reproductive parameters of a susceptible population of Rhipicephalus (B.) microplus females, using the Stall Test. The ticks were allocated randomly to treatments according to the mean numbers of females detached from each cow on days -3, -2 and -1 and the cattle pen location. The numbers of engorged female ticks that naturally detached from the cattle were counted daily from day 1 to day 30. For each group, 20 detached engorged female ticks or the available number collected daily were evaluated regarding reproductive parameters. Associations of organophosphates demonstrated elevated acaricidal efficacy, as well as deleterious effects on the reproductive parameters of R. (B.) microplus females. The engorged female weight (days 1 to 7), weight of egg masses (days 5 to 10) and larval hatching percentage (days 5 to 19) were decreased (P <= 0.05). It is possible that a formulation can lead to deleterious effects on R. (B.) microplus females when the tick population analyzed shows elevated sensitivity towards a particular formulation. However, further studies need to be conducted.

É relativamente pequeno o número de estudos que enfatiza os danos que uma formulação acaricida spray pode desencadear sobre os parâmetros reprodutivos das teleóginas. O presente estudo teve como objetivo avaliar os efeitos deletérios de uma formulação spray comercial (dichlorvos 60% + Clorpirifós 20%), sobre os parâmetros reprodutivos de uma população susceptível de R. (B.) microplus, desprendidas de bovinos experimentalmente infestados, utilizandose o teste de estábulo. Os animais foram alocados aos grupos de tratamentos de acordo com a contagem média de fêmeas desprendidas dos bovinos nos dias -3, -2 e -1. O número de teleóginas desprendidas foi quantificado do dia 1 ao 30. Para cada grupo, diariamente 20 fêmeas, ou a quantidade disponível, foram selecionadas e submetidas à avaliação dos parâmetros reprodutivos. A associação de organofosforados demonstrou elevada eficácia acaricida e também apresentou efeitos deletérios sob os parâmetros reprodutivos de Rhipicephalus (B.) microplus, diminuindo (P≤0,05) o peso das teleóginas (dos dias 1 ao 7), o peso da massa de ovos (dos dias 5 ao 10) e a eclodibilidade das larvas (dos dias 5 ao 19). Talvez uma formulação pode apresentar efeitos deletérios sobre os parâmetros reprodutivos de fêmeas de R. (B.) microplus, quando existe um elevado grau de sensibilidade dessa cepa de carrapato a um determinado composto. De qualquer maneira, futuros estudos devem ser realizados.
Keywords: Cattle tick; Dichlorvos 60% + chlorpyrifos 20%; Susceptible population; Reproductive efficiency; R. (B.) microplus